2009
DOI: 10.1002/hipo.20544
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent enhancement of inhibitory synaptic transmission in CA1 pyramidal neurons via GluR5 kainate receptors

Abstract: Changes in hippocampal synaptic networks during aging may contribute to age-dependent compromise of cognitive functions such as learning and memory. Previous studies have demonstrated that GABAergic synaptic transmission exhibits age-dependent changes. To better understand such age-dependent changes of GABAergic synaptic inhibition, we performed whole-cell recordings from pyramidal cells in the CA1 area of acute hippocampal slices on aged (24-26 months old) and young (2-4 months old) Brown-Norway rats. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Our previous study showed that there is glutamatergic tonic inhibition on GABAergic neurotransmission through the non-NMDA receptor, GluR5-containing kainate receptor. [14] In the present study, DNQX, a non-NMDA glutamatergic antagonist, significantly induced the increase of sIPSCs in the control and etomidate exposure groups, which suggests that there is glutamatergic tonic inhibition on GABAergic neurotransmission; etomidate exposure did not affect the glutamatergic tonic inhibition on GABAergic neurotransmission. However, DNQX did not induce the increase of sIPSCs in the propofol group, which suggests that there is no glutamatergic tonic inhibition on GABAergic neurotransmission, or impaired this pathway.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Our previous study showed that there is glutamatergic tonic inhibition on GABAergic neurotransmission through the non-NMDA receptor, GluR5-containing kainate receptor. [14] In the present study, DNQX, a non-NMDA glutamatergic antagonist, significantly induced the increase of sIPSCs in the control and etomidate exposure groups, which suggests that there is glutamatergic tonic inhibition on GABAergic neurotransmission; etomidate exposure did not affect the glutamatergic tonic inhibition on GABAergic neurotransmission. However, DNQX did not induce the increase of sIPSCs in the propofol group, which suggests that there is no glutamatergic tonic inhibition on GABAergic neurotransmission, or impaired this pathway.…”
Section: Discussionsupporting
confidence: 46%
“…[14] Briefly, the rat was decapitated and its brain was removed after sedation with isoflurane; transverse hippocampal slices (250–300 micrometer, thick) were cut in ice-cold sucrose-artificial cerebrospinal fluid (aCSF) with a VT1000S microtome (Leica, Deerfield, IL, USA). One to four slices were recorded from one rat and one cell was recorded in one slice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data generated from these measurements were used to plot cumulative probability amplitude and inter-event interval graphs, with each distribution normalized to a maximal value of 1. Cumulative probability plots obtained under different experimental conditions were compared using the nonparametric Kolmogorov –Smirnov test (KS-T), which estimates the probability that two cumulative distributions differ from each other by chance alone (Xu et al, 2009). All numerical values are expressed as mean ± standard error of the mean (SEM) and statistical analyses were performed by using a paired Student’s t -tests as needed.…”
Section: Methodsmentioning
confidence: 99%